Petrology and geochronology of eclogites from the Variscan Schwarzwald (F.R.G.) - Kalt, Angelika; Hanel, Michael; Schleicher, Helmut; Kramm, Ulrich (My University, 1994)
The Moldanubian basement of the Schwarzwald contains basic to ultrabasic rocks of both crustal and mantle origin which display high-pressure mineral assemblages or relics of such. In order to constrain the P-T-t evolution of the crustal high-pressure rocks, petrological and geochronological studies have been carried out on three eclogite samples. Geothermobarometric estimations indicate minimum metamorphic pressures of 1.6 GPa and equilibration temperatures of 670 750°C. Reaction textures document various metamorphic stages during exhumation of the high-pressure rocks. The age of high-pressure metamorphism is constrained by Sm-Nd isochrons of 332±13 Ma, 334±11 Ma, and 337±6 Ma defined by garnet, whole rock and clinopyroxene. For one sample, large garnets show prominent growth zoning in terms of major elements, Sm, Nd, and inclusions, dividing the grains into two growth stages. Sm-Nd isotope analyses on these garnets indicate that the time span between the two growth stages is too small to be resolved, reflecting a rather rapid metamorphic evolution. This result is further constrained by a Rb-Sr isochron age of 325±6 Ma on retrograde biotite and whole rock on the same sample. For one of the studied eclogites, formation of the magmatic precursor rocks is possibly approximated by the Ordovician U-Pb upper intercept age of a discordia from zircons.